The immune cell landscape of glioblastoma patients highlights a myeloid-enriched and immune suppressed microenvironment compared to metastatic brain tumors - Musca, Beatrice; Russo, Maria Giovanna; Tushe, Ada; Magri, Sara; Battaggia, Greta; Pinton, Laura; Bonaudo, Camilla; Della Puppa, Alessandro; Mandruzzato, Susanna (Frontiers in Immunology, 2023)
Introduction: Brain metastases (BrM), which commonly arise in patients with melanoma, breast cancer and lung cancer, are associated with a poor clinical prognosis. In this context, the tumor microenvironment (TME) plays an important role since it either promotes or inhibits tumor progression. Our previous studies have characterized the immunosuppressive microenvironment of glioblastoma (GBM). The aim of this study is to compare the immune profiles of BrM and GBM in order to identify potential differences that may be exploited in their differential treatment.Methods: Tumor and/or blood samples were taken from 20 BrM patients and 19 GBM patients.Multi-parametric flow cytometry was used to evaluate myeloid and lymphoid cells, as well as the expression of immune checkpoints in the TME and blood. In selected cases, the immunosuppressive ability of sorted myeloid cells was tested, and the ex vivo proliferation of myeloid, lymphoid and tumor cell populations was analyzed.Results: High frequencies of myeloid cells dominated both the BrM and GBM landscapes, but a higher presence of tumor-associated macrophages was observed in GBM, while BrM were characterized by a significant presence of tumor-infiltrating lymphocytes. Exhaustion markers were highly expressed in all T cells from both primary and metastatic brain tumors. Ex vivo analysis of the cell cycle of a single sample of a BrM and of a GBM revealed subsets of proliferating tumor cells and blood-derived macrophages, but quiescent resident microglial cells and few proliferating lymphocytes. Macrophages sorted from a single lung BrM exhibited a strong immunosuppressive activity, as previously shown for primary GBM. Finally, a significant expansion of some myeloid cell subsets was observed in the blood of both GBM and BrM patients. Discussion: Our results define the main characteristics of the immune profile of BrM and GBM, which are distinguished by different levels of immunosuppressive myeloid cells and lymphocytes devoid of effector function. Understanding the role of the different cells in establishing the metastatic setting is critical for improving the therapeutic efficacy of new targeted immunotherapy strategies.